POLICY FORMULATION FOR THE ESTABLISHMENT OF REGIONAL REGULATIONS ON THE EMPOWERMENT, DEVELOPMENT AND PROTECTION OF MICRO ENTERPRISES IN SAMARINDA CITY - Ernita, Lina; Daryono, Daryono; Saipul, Saipul (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study aims to identify policy formulation and inhibiting factors in the formation of local regulations related to the Empowerment, Development, and Protection of Micro Enterprises in Samarinda City. This study uses a qualitative descriptive method, collecting data from several sources such as interviews, official documents, and field observations. The findings show that this policy serves as a form of support for national regulations and solutions to overcome various problems faced by micro business actors in Samarinda City. However, the process of forming this regional regulation still encounters several obstacles: lack of human resource capabilities, lack of communication between DPRD leaders and Bapemperda members, lack of commitment and inefficient time management during the formulation process, and the absence of permanent regulations that regulate the work mechanism and stages of the formation functionThis study recommends capacity building for DPRD members and AKD Support Staff, improving effective communication between the Leadership and Bapemperda, improving integrated time management, and establishing special DPRD regulations that regulate the procedural rules and mechanisms of the regional regulation formation process.